Pandangan Santri Mahad Aly tentang Pengarus-utamaan Gender di Pesantren Salafiyah Syafiiyah Sukorejo, Situbondo, Jawa Timur - Mufidah Ch. Mufidah Ch. (Islamica: Jurnal Studi Keislaman, 2009)
Gender discourse does present particular problems within Muslim societies mainly for three reasons, (1) the strong presence of patriarchal culture within Muslim society (2) the strong literal tendency in interpreting religious texts, and (3) the strong sense of animosity toward the Western culture. There is a few however among Muslims in Indonesia who are willing to negotiate with gender issues not as a discourse but as a practical principles that should rather be applied in our daily life. For this group of people patriarchal culture and literal interpretation of religious texts are problematic. This group thinks that the idea of gender equality is an inherent part of Islam and must therefore be accepted. Among this few is the students of Ma?had Aly in the East Javanese town of Situbondo. These students are concerned with implementation issues of gender equality rather than with debating this problem as a discourse. This paper explores the ideas of these students and relates them with the general debate that takes place on the national level concerning the issue of gender equality.